Faixas foliares e normas DRIS para solo e folha : de pimenteira do reino no norte do Espírito Santo - Fardim, Vinicius Miotto (2023)
Black pepper is a perennial plant, from the Piperaceae family, native to India. It is a crop that requires balanced nutrition, so knowing the nutritional contents helps to contribute to the nutritional adjustment of the crop in its production cycle. Several strategies are used to evaluate the nutritional status of crops, so foliar analysis is frequently adopted, using the plant itself as an extractor. In relation to nutritional diagnosis, several methods are used, highlighting the sufficiency range and DRIS. In this sense, the objective was to establish nutritional standards for black pepper grown in the north of Espírito Santo/ES., of the Bragantina variety. 26 commercial crops were used, cultivated in full sun with drip and microjet irrigation, with all cultural treatments carried out, from cleaning to phytosanitary control. Thus, the leaf contents of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn were determined in 26 conventionally cultivated crops, followed by the Lilliefors test, establishing the value of 1 %, to check the normality of the values referring to the levels of each nutrient. The differences obtained between the norms (standard deviation, mean and coefficient of variation of nutrients and their relationships between other nutrients) were used using the F test (Anova). Through this test among the 110 nutritional relationships, 61 are similar (p≤0.05), and 49 of the nutritional indices differ between the leaf sampling periods. Differences found confirmed that the sufficiency ranges and DRIS standards must be specific for each season and region